De Pearson a Spearman (2007)
ABSTRACT: article is about the Pearson and Spearman correlation coefficients which are widely used in agricultural sciences in order to establish the relationships between generally quantitative variables. It also contains the fundamental assumptions in which the Pearson method is based: bivariated normality, variable interaction linearity, as well as the programming Schedule in SAS software; in addition, the way in which SAS exits must be interpreted which oscillate between -1 ≤ ρ ≤ 1.